A family of small, cyclic peptides buried in preproalbumin since the Eocene epoch. (28th February 2018) - Fisher, Mark F.; Zhang, Jingjing; Taylor, Nicolas L.; Howard, Mark J.; Berkowitz, Oliver; Debowski, Aleksandra W.; Behsaz, Bahar; Whelan, James; Pevzner, Pavel A.; Mylne, Joshua S.
Abstract: Orbitides are cyclic ribosomally synthesized and post‐translationally modified peptides from plants; they consist of standard amino acids arranged in an unbroken chain of peptide bonds. These cyclic peptides are stable and range in size and topologies making them potential scaffolds for peptide drugs; some display valuable biological activities. Recently, two orbitides whose sequences were buried in those of seed storage albumin precursors were said to represent the first observable step in the evolution of larger and hydrophilic bicyclic peptides. Here, guided by transcriptome data, we investigated peptide extracts of 40 species specifically for the more hydrophobic orbitides and confirmed 44 peptides by tandem mass spectrometry, as well as obtaining solution structures for four of them by nuclear magnetic resonance. Acquiring transcriptomes from the phylogenetically important Corymbioideae subfamily confirmed the precursor genes for the peptides (called PawS1‐Like or PawL1 ) are confined to the Asteroideae, a subfamily of the huge plant family Asteraceae. To be confined to the Asteroideae indicates these peptides arose during the Eocene epoch around 45 Mya. Unlike other orbitides, all PawL‐derived Peptides contain an Asp residue, needed for processing by asparaginyl endopeptidase (AEP). This study has revealed what is likely to be a very large new family of orbitides, uniquely buried alongside albumin and processed by AEP.